Effects of deep thermotherapy on chest wall mobility of healthy elderly women. (2nd April 2020) - Bito, Tsubasa; Suzuki, Yusuke; Kajiwara, Yuu; Zeidan, Hala; Harada, Keiko; Shimoura, Kanako; Tatsumi, Masataka; Nakai, Kengo; Nishida, Yuichi; Yoshimi, Soyoka; Kawabe, Rika; Yokota, Junpei; et al.
ABSTRACT: Chest wall mobility decreases with age in community-dwelling women aged 65 years or older. Thermotherapy is used to improve soft-tissue extensibility. However, its effects on chest wall mobility are unclear. This study aimed to examine the effect of thermotherapy on chest wall mobility in healthy elderly women. Twenty-eight elderly women participated in this study. Chest wall mobility at three levels (axillary, xiphoid, and tenth rib), respiratory function (forced vital capacity and forced expiratory volume), and tissue temperature (skin temperature (ST)) and deep temperature (DT) with 10 mm and 20 mm depth from the skin (10 mm DT and 20 mm DT)) were measured before and after 15 minutes of thermotherapy. The subjects randomly received one of the three interventions (capacitive and resistive electric transfer (CRet), hot pack (HP), and sham CRet (sham)). Chest wall mobility at all levels significantly increased after CRet intervention. Hot pack significantly increased tenth rib excursion; it also significantly increased ST, 10 mm DT, and 20 mm DT, whereas CRet significantly increased 10 mm DT and 20 mm DT. There were significant differences between CRet, HP, and sham in ST, 10 mm DT, and 20 mm DT. Furthermore, 20 mm DT had increased more in CRet than in HP. CRet improved chest wall mobility at all levels and HP improved at the tenth rib level. This implies that CRet can be one of the approaches to improve chest wall mobility.